Mapping Religious Moderation and Its Impact on Islamic Education in Indonesia: A Bibliometric Approach - Zamroni, Edris; Handayani, Puji Gusri; Gudnanto; Lestari, Indah; Azis, Akhmad Rifqi; Kumara, Agus Ria (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
As a country with high religious and cultural diversity, Indonesia makes religious moderation a crucial issue in maintaining harmony and tolerance between religious communities. In this increasingly complex context, research on religious moderation is becoming increasingly relevant. It is necessary to conduct a study that allows us to comprehensively map the publications that have been carried out related to religious moderation to see research trends, dominant topics, and knowledge gaps that still need to be filled. This study aims to get an overview of the trend of religious moderation research in various contexts and scientific perspectives. The research was conducted by collecting multiple articles that have been published and indexed on the reputable database scopus.com. The data obtained was analyzed using bibliometric analysis with the help of R Studio bibliophily. The results obtained 113 data published in the period 2007 to 2024. Based on visual analysis, it is known that religious moderation related to gender is the dominant issue in the period 2012-2024. In addition, there are unique themes related to local wisdom, education curriculum, and human rights. Indonesia is the most preferred country for diverse moderation research, and the dominant number of publications from Indonesian researchers and educational and research institutions in Indonesia reinforces this. However, not much research has attempted to build cross-country networks, so it is necessary to conduct cross-country and cross-religious studies for religious moderation research in the future.